The Great War : a photographic narrative - Holborn, Mark, 1949-; Roberts, Hilary (Curator); Imperial War Museum (Great Britain) (New York : Alfred A. Knopf : Imperial War Museums, 2013)
"On the occasion of the centenary of World War I in August 2014--an unprecedented, spectacular pictorial history of the first global war in 380 black-and-white photographs, many never seen before, from Imperial War Museums. This monumental, dramatic photographic narrative captures the war from the early arms race that developed around the massing of prewar battleship fleets to the final moments of the conflict with the sinking of the German fleet in Scapa. The photographs span the many battlefronts throughout the world: from the British Isles to the south Atlantic, across Europe and the Ottoman Empire, Sudan and East Africa, Jerusalem and Damascus. Here are soldiers from across the globe, vast battleships, dirigibles overhead, the streets of London, the first battle of Ypres, German submarines at sea, the beaches of Gallipoli, the battle of Jutland, the battle of the Somme trenches, and much, much more"--
An editorial note / Mark Holborn -- June 1914-December 1914 -- January 1915-January 1916 -- February 1916-December 1916 -- January 1917-December 1917 -- January 1918-November 1918 -- Photography in the Great War / Hilary Roberts.
"This is a Borzoi book"--Colophon.
"Published by Alfred A. Knopf in association with Imperial War Museums"--Colophon.
Keywords: World War, 1914-1918 -- Pictorial works; World War, 1914-1918 -- Photography; World War, 1914-1918 -- Chronology; Imperial War Museum (Great Britain) -- Photograph collections; Imperial War Museum (Great Britain)